PENERAPAN OPTICAL CHARACTER RECOGNATION PADA PENTERJEMAH INGGRIS â INDONESIA MOBILE BERBASIS AUGMENTED REALITY - DEW, ossy; Zaini, T.M.; Frizka, Frizka (Jurnal Informatika, 2013)
In general a translator use keypad or keyboard as input device. Sometimes user getting trouble when he or she must type long word or sentence. A new way to solve that problem is using Optical Character Recognation (OCR). In this research we developed English -Â  Indonesian, Indonesian - English translator using OCR and Augmented Reality. This application running well in Android flatform, when support of good lighting and particular camera distance and point of view. This application have two output, namely text and sound which realized by Augmented Reality technology . Keyword : Translator, Optical Character Recognation, Augmented reality.